Correlation Is Not Prediction: Reassessing Predictive MRI Evidence in Guidelines for Persons With Relapsing-Remitting Multiple Sclerosis. - Minas, Dulat; Buchka, Stefan; Havla, Joachim; Mansmann, Ulrich (Journal of Central Nervous System Disease, 2026)
Background: Effective treatment monitoring and treatment decisions in relapsing-remitting multiple sclerosis (RRMS) require accurate and individualized prediction of future disease courses. Guidelines from the Magnetic Resonance Imaging in Multiple Sclerosis (MAGNIMS) group and the Canadian Multiple Sclerosis Working Group (CMSWG) frequently cite MRI outcomes as predictive, but the methodological quality of this evidence is uncertain. Objectives: This study aims to critically assess the methodological standards underlying predictive claims about MRI outcomes in four major relevant MS guidelines. Design: We conducted a content review of citations in the MAGNIMS 2015 and 2021 and the CMSWG 2013 and 2020 guideline publications. Methods: Each source was evaluated for whether it reported quantitative predictive evidence: either predictive values with confidence intervals, Kaplan–Meier–based risk estimates, or externally validated models that provide accurate risk estimates (good calibration) and correctly separate high- from low-risk patients (good discrimination); We also checked if measures such as correlations, odds ratios, hazard ratios, Prentice criteria, or likelihood ratio tests were used. Results: Across all four guidelines, most predictive statements relied on secondary citations and association-based measures. Odds ratios, hazard ratios, correlations, or Prentice criteria were commonly reported. Some studies reported predictive values, but confidence intervals were frequently not provided. Only isolated examples of properly validated prediction models were cited, and only one had undergone full external validation. Advanced methods, such as the likelihood reduction factor, were absent. Conclusion: Current guideline statements on MRI prediction in RRMS often rely on associations rather than validated individualized predictions. They do not quantify individual risk or provide evidence for accuracy, calibration, discrimination, or robustness (reliability of predictions across different patients and settings). To ensure trustworthy and actionable evidence, future guidelines should require prospective risk estimates with confidence intervals, externally validated models with calibration and discrimination, predefined thresholds for predictive usefulness, and evaluation of clinical utility (e.g., decision curve analysis). Plain Language Summary: Why was the study done? To effectively treat relapsing-remitting multiple sclerosis (RRMS), reliable individualized prediction of disease worsening based on MRI findings is needed. Four widely used guidelines cite sources that provide such predictive information. However, it is unclear if the presented evidence supports good individual predictions. Thus, this study aims to assess the quality of predictive information in the literature cited by the guidelines on the prediction quality of MRI in RRMS. What did the researchers do? The sources claiming predictive ability of MRI in two guidelines from the Magnetic Resonance Imaging in Multiple Sclerosis (MAGNIMS) group and two guidelines from the Canadian Multiple Sclerosis Working Group (CMSWG) were extracted. The objectives, methodology, and content of the sources were analyzed. The methodologies were then grouped into ten statistical categories, and each category was assessed for its quality in individual prediction. What did the researchers find? In total, 75 sources were identified, which were directly or indirectly cited in the guidelines to show the predictive quality of MRI information. About 80% of sources used association measures to show individual prediction. The cited evidence was mostly insufficient to enable clinically relevant individual predictions. Neither groups report the quality of evidence they used in their guidelines. They also do not report measures for uncertainty of estimates (e.g., confidence intervals). However, one study included an independently tested model, while one other study used a statistically sound prediction model. What do these findings mean? Current guideline statements on MRI prediction in RRMS often rely on associations and rarely employ well-validated methods. There is a need for the Multiple Sclerosis scientific community to set minimum standards for the evidence accepted to support individualized prediction and to rank and assess the contribution of each evidence.